On the Use of Passive Reflecting Surfaces and Compressive Sensing Techniques for Detecting Security Threats at Standoff Distances - Yolanda Rodriguez-Vaqueiro; Jose Angel Martinez-Lorenzo (International Journal of Antennas and Propagation)
This work presents a new radar system concept, capable of detecting explosive related threats at standoff distances. The system consists of a two-dimensional aperture of randomly distributed transmitting/receiving antenna elements and a set of passive reflecting surfaces (PRS) positioned in the vicinity of the target. The PRS act as a mirror that enhances the field of view of the radar system, thus increasing its resolution. A 3D imaging algorithm, based on novel compressive sensing techniques, is used in this work. This system configuration provides a resolution of 7.1 mm in cross-range and 25 mm in range, when the target is at 10 m range, and the radar works at 60 GHz center frequency and has 6 GHz bandwidth.